Implementation of Contract Law in Resolution of Business Contract Disputes in Indonesia - Khairani Alawiyah Matondang; Mery Kristiani Susanti; Salma Diani; Aisyah Fadillah Lubis (SEAN Institute, 2026)
This article discusses the implementation of obligations law in resolving business contract disputes in Indonesia using a normative juridical approach. The study highlights the role of the Civil Code (KUHPerdata) in providing legal certainty regarding the rights and obligations of the parties as well as mechanisms for dispute resolution arising from default. The analysis includes basic principles of agreements, such as pacta sunt servanda, good faith, and freedom of contract, which serve as the foundation for contract interpretation and legal protection for the agreed party. The article examines dispute resolution through both litigation and non-litigation means, including mediation, arbitration, and consensual approaches, along with their advantages and limitations. The findings indicate that the application of obligations law is effective in enforcing contracts and regulating the rights and obligations of parties in business contracts, but it still requires consistent interpretative guidelines to reduce the risk of legal uncertainty. This research provides theoretical and practical insights for business practitioners, lawyers, and legal academics in understanding and implementing dispute resolution mechanisms for business contracts fairly and in accordance with the principles of Indonesian civil law.